Students' Errors in Solving Mathematical Statistics Problems Based on Sensing and Intuiting Personality Types - Anggraini, Syarifa; Nasution, Eline Yanty Putri (Department of Mathematics Education Program IPI Garut, 2025)
Kesalahan mahasiswa dalam menyelesaikan soal statistika matematika menjadi salah satu indikator rendahnya pemahaman konsep statistik di perguruan tinggi. Penelitian ini difokuskan pada analisis pola kesalahan yang dilakukan oleh mahasiswa saat mengerjakan soal statistika matematika, dengan mempertimbangkan tipe kepribadian sensing dan intuiting. Dalam studi kasus ini, sebanyak 36 siswa dengan tipe kepribadian sensing dan intuiting turut serta sebagai partisipan. Instrumen penelitian mencakup tes kepribadian MBTI (Myers-Briggs Type Indicator), tes kemampuan statistika, pedoman wawancara semi-terstruktur, dan lembar observasi. Data dianalisis melalui kondensasi data, penyajian data, dan penarikan Kesimpulan secara interaktif. Temuan penelitian mengungkapkan bahwa mahasiswa dengan tipe kepribadian sensing lebih sering melakukan kesalahan pada tahap transformasi dan encoding, sedangkan tipe intuiting lebih sering salah dalam keterampilan proses dan encoding. Temuan ini mengindikasikan bahwa tipe sensing kesulitan mengubah informasi verbal menjadi model matematika, sementara intuiting kurang sistematis dalam penyelesaian dan penyajian jawaban. Dengan demikian, pola kesalahan mahasiswa dalam mengerjakan soal statistika matematika dipengaruhi oleh tipe kepribadian mereka. Student errors in solving mathematical statistics problems are one indicator of the low level of conceptual understanding of statistics in higher education. This study focuses on analysing the patterns of errors made by students when working on mathematical statistics problems, taking into account their sensing and intuitive personality types. In this case study, as many as 36 students with sensing and intuiting personality types participated as participants. The research instruments included the MBTI (Myers-Briggs Type Indicator) personality test, a statistics ability test, semi-structured interview guidelines, and observation sheets. The data were analysed through data condensation, data display, and interactive conclusion drawing. The findings of the study revealed that students with sensing personality types are more likely to make mistakes at the transformation and encoding stages, while intuiting types more frequently made errors in process skills and encoding. These findings suggest that sensing types struggle to convert verbal information into mathematical models, while intuiting types are less systematic in their problem-solving procedures and in presenting final answers. Thus, the pattern of students' mistakes in doing mathematical statistics problems is influenced by their personality type.